Efeitos dos subprodutos da aroeira e do biofilme a base de quitosana na pós-colheita e controle da antracnose em goiabas ‘Paluma’ - Santos, Marília Cavalcante dos (2012)
Guava is cultivated in many parts of the world, but the high perishability and the incidence of diseases such as anthracnose limits its commercialization. The challenge to the method used to attempt to solve these problems, the use of chemicals, has instigated the conduct of research with products. Thus, plantas have been studied mant times have active substances with antimicrobial properties, among them aroeira that is widely used in folk medicine and its potencial for the use in agricultura are being targeted studies. Another alternative is the use of coatings based on polymers such as chitosan that in addition to prolonging the shelf-life also presents potencial antifungal. This study to determine the yeld of aqueous extract and hydrolate mastic and the main chemical compounds contained, to evaluate the antifungal effect of hydrodistillation byproducts on in vitro development of the fungus Colletotrichum gloeosporioides and test biofilm-base chitosan for promote increased service life and control the attack of anthracnose in guavas Paluma . The aqueous extract end hydrolate were obtained by hydrodistillation of leaves and seeds at different times. For the in vitro antifungical power of aroeira in C. gloeosporioides concentrations used were 5, 10, 15, 20, 25 and 30% aqueous extraxt, 10, 15, 20 and 25% hydrolate and 2μL fungicide. In vivo test, guavas were inoculated with the pathogen were for 1 minute in chitosan solutions 2, 3 and 4% and subjected to chemical and physical assessments every 4 days storage totaling 12. It was observed that the time of hydrodistillation did not influence the yeld of the aqueous extract and hydrolate, indicating 2,5h for extraction. Larger amounts of hidrolact were obtained from levaes of aroeira, while the yield of the extract was not influenced by the plant. Unable to determine the compounds existing in the hydrolate aroeira. The fungus developed in all treatments with respect cotonoso except in fungicide Captan® (2μL). The aqueous extract and hydrolate aroeira showed no fungicidal properties of inhibiting the development of in vitro concentrations used in Colletotrichum gloeosporioides is not recommended to control of this fungus. The guavas coated with chitosan 3 and 4% had delayed ripening being evidenced by the high firmness, color maintenance from the pulp and peel, slight increase of soluble solids and vitamin C in addition to having constant pH. A 2% chitosan was not as efficient when compared to other concentrations. The fruits control and fungicide were not fit for consumption for 12 days due to the rapid maruration and incidence of anthracnose. All concentrations of chitosan were efficient in controlling the fungus.